Unlocking Prosperity: Identifying Key Sectors For Tourism Development In Yogyakarta - Wiguna, Yordan; Dewi, Ine Ratna; Noya, Avior Ocean Louis Ishaac (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2024)
Tourism has great potential to create jobs and improve Indonesia's competitiveness in the global market. The Special Region of Yogyakarta (DIY) is one of the provinces in Indonesia that has comparative advantages and good prospects in tourism. This study aims to determine the economic sectors that are the basis and have prospects for growth and to determine the development that can be done in these sectors to optimize tourism in each regency and city in the Special Region of Yogyakarta. Based on analysis using Location Quotient (LQ) and Dynamic Location Quotient (DLQ), the agriculture, forestry, and fisheries sector, the water supply, waste management, waste, and recycling sector, the wholesale and retail trade sector, car and motorcycle repair, the transportation and warehousing sector, as well as the accommodation and food supply sector are the basic and prospective sectors in the regencies and cities in Yogyakarta. Optimization of tourism can be done through the intensification of these basic and prospective sectors through strengthening agro-tourism, waste management, local shopping, and public transportation in each district and city in DIY. By strengthening the basic sectors and taking strategic steps in tourism development, DIY can strengthen its position as an attractive and sustainable tourism destination.